Do Intellectual Capital and Financial Performance Mitigate Financial Distress: Evidence from Kompas 100 Companies on the Indonesia Stock Exchange - Nidia Anggreni Das; Juita Sukraini; Dilla Ramadhani Fitri (Rescollacom (Research Collaborations Community), 2026)
His study aims to determine the effect of Intellectual Capital (X1) and Company Financial Performance (X2) on Financial Distress (Y). The results of the study indicate that there is an influence of Intellectual Capital (X1) on Financial Distress (Y). The results of the first hypothesis test are proven by the value of 6,651 ≥ 1,97944 and a t significance of 0,000 < 0,05. After that, there is an influence of Company Financial Performance (X2) on Financial Distress (Y). The results of the second hypothesis test are proven by the value of 18,250 ≥ 1,97944 and a t significance of 0,000 < 0,05. In addition, there is a simultaneous influence of Intellectual Capital (X1) and Company Financial Performance (X2) on Financial Distress (Y). The results of the third hypothesis test are proven by the value of 70,029 ≥ 3,07 and a significance F of 0,000 < 0.05. Companies with intellectual capital tend to have operational efficiency, The synergy between optimal intellectual capital management and good financial performance will strengthen the company's financial condition and minimize the risk of financial distress.